Excessive erythrocytosis and deep superior extremity venous thrombosis: a case purpose - Díaz-Lazo, Aníbal (2019)
Deep vein thrombosis of the upper extremities is a rare clinical entity. The secondary causes associated with more frequency are: the presence of central venous catheter and cancer. A case of deep vein thrombosis of the upper extremities was reported that was related to the fall suffered with probable trauma of the subclavian vein and the excessive erythrocytosis he suffered. The diagnosis was made with duplex ultrasound. The anticoagulant treatment used was with low molecular weight heparin at the beginning and subsequently with warfarin. The patient evolved favorably. In people who live in height, and develop  excessive erythrocytosis, this could be an important factor in the genesis of deep vein thrombosis of the upper extremities.